DECODING DEFERRED TAX EXPENSE: ITS IMPACT ON TAX AVOIDANCE THROUGH THE LENS OF FOREIGN OWNERSHIP - Ahmad Bukhori Muslim; Tirin Wulandari; Dian Sulistyorini Wulandari (ZILLZELL MEDIA PRIMA, 2025)
This study examines the effect of deferred tax expenses on tax avoidance, with foreign ownership as a moderating variable. The purpose of this research is to understand how deferred tax expense influences corporate tax avoidance and how foreign ownership moderates this relationship. The study uses panel data regression on a sample of firms from various industries, covering the period from 2020 to 2022. The analysis includes testing for model suitability using the Hausman test and the Lagrange Multiplier (LM) test. The findings indicate that deferred tax expense has a significant positive effect on tax avoidance. Moreover, foreign ownership significantly moderates this relationship, enhancing the impact of deferred tax expenses on tax avoidance. The study suggests that while foreign ownership may reduce tax avoidance directly, it strengthens the relationship between deferred tax planning and tax avoidance, emphasizing the role of ownership structure in tax strategy formulation.